2016
DOI: 10.1002/cne.24032
|View full text |Cite
|
Sign up to set email alerts
|

Posterior parietal cortex of the rat: Architectural delineation and thalamic differentiation

Abstract: This study refines the characterization of the rat parietal cortical domain in terms of cyto‐ and chemoarchitecture as well as thalamic connectivity. We recognize three subdivisions of the posterior parietal cortex (PPC), which are architectonically distinct from the neighboring somatosensory and visual cortices. Furthermore, we show that the different parietal areas are differently connected with thalamic nuclei. The medial portion of PPC (mPPC) is connected primarily with the medial portion of the lateral po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 91 publications
(173 reference statements)
6
71
2
Order By: Relevance
“…Importantly, we reconciled widely used but disparate nomenclatures that refer to PPC (Paxinos & Franklin, ) versus the extrastriate areas around it (Montero, ; Olavarria & Montero, ; Olavarria et al., ; Wang & Burkhalter, ). We further confirmed our coordinates for PPC on the basis of projections to associative thalamic nuclei, which corresponded to thalamic projection patterns in rats (Bucci et al., ; Chandler et al., ; Kolb & Walkey, ; Olsen & Witter, ), mice (Harvey et al., ) and several other mammalian species (Donoghue & Ebner, ; Olson & Lawler, ; Padberg & Krubitzer, ; Schmahmann & Pandya, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Importantly, we reconciled widely used but disparate nomenclatures that refer to PPC (Paxinos & Franklin, ) versus the extrastriate areas around it (Montero, ; Olavarria & Montero, ; Olavarria et al., ; Wang & Burkhalter, ). We further confirmed our coordinates for PPC on the basis of projections to associative thalamic nuclei, which corresponded to thalamic projection patterns in rats (Bucci et al., ; Chandler et al., ; Kolb & Walkey, ; Olsen & Witter, ), mice (Harvey et al., ) and several other mammalian species (Donoghue & Ebner, ; Olson & Lawler, ; Padberg & Krubitzer, ; Schmahmann & Pandya, ).…”
Section: Discussionsupporting
confidence: 84%
“…As with rats, PPC in the mouse is located between visual and somatosensory cortices (Paxinos & Franklin, 2012), and the existing data suggests that it has similar patterns of cortico-cortical and thalamic connectivity (Harvey et al, 2012;Kolb & Walkey, 1987;Oh et al, 2014;Olsen & Witter, 2016;Reep et al, 1994;Wilber, Clark, Demecha et al, 2014). More detailed aspects of mouse PPC anatomy, including the boundaries which distinguish it from neighboring areas, its laminar organization and chemoarchitectural profile remain ill-defined.…”
Section: Introductionmentioning
confidence: 99%
“…The PPC and V2 and their respective subdivisions are cytoarchitectonically distinct areas with different thalamic connections (Olsen and Witter, ). It is therefore noteworthy that all areas appear to be reciprocally connected to all divisions of the PHR and to RSC area 30, albeit with subtle topographical differences (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The lateroposterior thalamus, which is often characterized as a rodent homologue to the mammalian pulvinar, generally has a stronger reciprocal relationship with primary and secondary visual cortical regions (Nakamura et al, 2016;Roth et al, 2016). For instance, some recent work has indicated that the lateroposterior thalamus constitutes the strongest thalamic output to postrhinal and posterior parietal regions Nakamura et al, 2015;Olsen & Witter, 2016;Pereira et al, 2016), perhaps suggesting that this region has a greater role in guiding orientation in relation to visual-spatial targets.…”
Section: Subregions and Connectivitymentioning
confidence: 95%
“…A final consideration that has received limited attention is whether the anterior and lateral thalamus might have a role in spatial and contextual representations in postrhinal and parietal cortical targets (Olsen & Witter, 2016;Pereira et al, 2016;Wilber et al, 2015). For instance, the parietal cortex contains directionally modulated neural populations that fire in a distal spatial framework , but also contains neural populations that fire in relation to egocentric body-turns and egocentric relationship with proximal visual cues (McNaughton et al, 1993).…”
Section: Summary Conclusion and Unanswered Questionsmentioning
confidence: 97%